UJI AKTIVITAS ANTIOKSIDAN RUMPUT JUKUT PENDUL (Kyllinga nemoralis) - Nabila, Regina Syifa; Soemarie, Yulistia Budianti; Ramadhani, Juwita (Jurnal Buana Farma, 2025)
Antioxidants are compounds that play an important role in preventing the impact of free radicals that cause various degenerative diseases. Synthesized antioxidants have carcinogenic properties over a long period of time, hence the need for natural sources of antioxidants that have fewer side effects. Jukut pendul grass (Kyllinga nemoralis) is one of the wild plants that has potential as a natural antioxidant. This study aims to compare the antioxidant activity of ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction of jukut pendul grass (Kyllinga nemoralis). The steps of this research were samples of jukut pendul grass (Kyllinga nemoralis) obtained from Kota Baru, South Kalimantan in maceration with 70% ethanol then fractionated using 3 solvents of different polarity. Antioxidant activity testing was performed with a Uv-Vis spectrophotometer using the DPPH method at a wavelength of 515 nm. The results showed that the IC50 value of ethanol extract was 79,842 + 14,275 µg/mL, n-hexane fraction 95,632 + 8,152 µg/mL, ethyl acetate fraction 42,616 + 1,972 µg/mL and water fraction 67,384 + 11,678 µg/mL. Based on the IC50 value, jukut pendul grass (Kyllinga nemoralis) has antioxidant activity with the highest activity in the ethyl acetate fraction.